A Mediterranean cold front identification scheme combining wind and thermal criteria. (26th May 2021) - Bitsa, Evangelia; Flocas, Helena A.; Kouroutzoglou, John; Galanis, George; Hatzaki, Maria; Latsas, George; Rudeva, Irina; Simmonds, Ian
Abstract: The goal of this study is to advance an automated and objective scheme for the identification of cold fronts over the Mediterranean based on wind‐related criteria, MedFTS, by further incorporating thermal criteria, in order to improve the identification of cold fronts on a climatological basis. These thermal criteria are related to cold advection and the thermal front parameter, and their individual or combined contribution is systematically investigated considering different threshold values. For each combination of thermal criteria and/or threshold values, the results are validated with the aid of statistical indices and metrics, and the optimum scheme configuration for the identification of Mediterranean fronts is selected. The advanced version of MedFTS, named MedFTS_DT, having incorporated both dynamic and thermodynamic criteria, is applied and validated for a decade of fronts over the Mediterranean. It was found that the number of erroneously identified cold fronts over Greece was significantly reduced from MedFTS to MedFTS_DT version by almost 40%, as indicated by the statistical metrics. Therefore, the performance of MedFTS_DT is verified to be superior to MedFTS. As a further attempt to investigate the ability of MedFTS_DT to perform adequate climatological analysis in the Mediterranean, the frequency of the cold fronts was calculated over Greece during the period 2007–2016 on a monthly and seasonal basis, demonstrating that the scheme can capture the intra‐annual variations. Finally, the contribution of the cold fronts to the precipitation over the Mediterranean for the same period was investigated, further supporting the scheme's performance. Abstract : A frontal identification scheme was developed to identify cold fronts in the Mediteranean on a climatological basis, named MedFTS_DT scheme employing wind and thermal criteria. It was found that the wind criteria are prerequisites for the identification of Mediterranean cold fronts, while the thermal criteria provide a stricter filter that serves to limit the initial number of identified fronts. The scheme appears to be an effective tool for the generation of an objective climatology of cold fronts in the Mediterranean. (a) Synoptic surface chart over the area of interest at 12:00 UTC 4 October 2008. (b) Identified fronts at 12:00 UTC 4 October 2008. The red lines show the identified fronts. Green colour shows where only the wind criteria are satisfied, whereas blue indicates where both wind and thermal criteria are satisfied. The black dotted line shows the region of Greece.